DETERMINANT ANALYSIS OF THE NET BENEFITS OF THE USE OF SAKTI: USER SATISFACTION MEDIATION - Azwar Iskandar; Tenry Nur Amriani (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to analyze the effect of system quality, information quality, and service quality of the system on net benefits of SAKTI implementation mediated by user satisfaction. The study uses primary data obtained from 112 respondents at the working units in the BPPK through questionnaires using the purposive sampling technique. This study uses path analysis technique. The type of research is causal explanatory using inferential statistical analysis technique in the form of path analysis. The results showed that the quality of the system, the quality of information and service quality from the implementation of the SAKTI proved empirically not able to provide user satisfaction and optimal net benefits. The quality of the system affects the user satisfaction and user satisfaction also affects the net benefits. However, the quality of information and service quality does not affect the satisfaction of SAKTI users in an integrated way. User satisfaction cannot be a intervening variable between service quality and the net benefit obtained. DJPB is expected to improve the quality of information and services thoroughly and continuously so that the user satisfaction and the benefits of SAKTI can be obtained optimally.